PscCYP716A1-Mediated Brassinolide Biosynthesis Increases Cadmium Tolerance and Enrichment in Poplar - Tian, Feifei; Han, Chengyu; Chen, Xiaoxi; Wu, Xiaolu; Mi, Jiaxuan; Wan, Xueqin; Liu, Qinglin; He, Fang; Chen, Lianghua; Yang, Hanbo; Zhong, Yu; Qian, Zongliang; et al. (Frontiers in Plant Science, 2022)
Cadmium (Cd), as one of the heavy metals with biological poisonousness, seriously suppresses plant growth and does harm to human health. Hence, phytoremediation was proposed to mitigate the negative effects from Cd and restore contaminated soil. However, the internal mechanisms of detoxification of Cd used in phytoremediation are not completely revealed. In this study, we cloned the cytochrome P450 gene PscCYP716A1 from hybrid poplar “Chuanxiang No. 1” and found that the PscCYP716A1 was transcriptionally upregulated by Cd stress and downregulated by the exogenous brassinolide (BR). Meanwhile, PscCYP716A1 significantly promoted the poplar growth and enhanced the Cd accumulation in poplar. Compared to wild-type poplars, overexpressed PscCYP716A1 lines produced higher levels of endogenous BR and showed a stronger tolerance to Cd, which revealed that PscCYP716A1 may reduce the oxidative stress damage induced by Cd stress through accelerating BR synthesis. In general, PscCYP716A1 has a potential superiority in regulating the plant's tolerance to Cd stress, which will provide a scientific basis and a new type of gene-modified poplar for Cd-pollution remediation.